Light-level geolocation reveals the short-distance non-breeding movements and distribution of tufted puffins throughout the Northeast Pacific Ocean - Schaefer, Anne L.; Gorman, Kristen B.; Bishop, Mary Anne (Frontiers in Marine Science, 2022)
Comprehensive assessments of cumulative impacts to seabirds have been hindered by an incomplete understanding of temporal and spatial patterns in marine habitat use, particularly during the non-breeding season when seabirds can range widely across the global ocean. Alcids are an important component of the meso-predator biodiversity of the North Pacific Ocean, yet the non-breeding movement ecology and distribution for many of the Pacific Auk species remain poorly quantified. Recent and projected declines for historically robust populations of tufted puffin (Fratercula cirrhata) in Alaska highlight the importance of resolving aspects of the species’ non-breeding ecology, especially the pelagic phenology and distribution. We used light-level geolocation to quantify the annual at-sea distribution of tufted puffins between a major Gulf of Alaska nesting colony (Middleton Island) and heretofore unknown migration routes and wintering areas. Geolocator data from 42 complete migration routes of reproductive adult tufted puffins collected primarily between 2018-2020 revealed that both males and females were short-distance migrants, wintering on average 616 km from their breeding colony. Tufted puffins departed the breeding grounds in early September. Males made fewer stops and arrived earlier to wintering areas than females, however the arrival date to the wintering area was later in 2019 compared to 2018. Males took 30.5 ± 16.7 (± standard deviation) days in 2018 and 30.8 ± 24.6 days in 2019 to arrive at wintering areas. Conversely, females took 36.1 ± 16.8 days in 2018 and 59.8 ± 17.3 days in 2019 to arrive at wintering areas. Adult tufted puffins wintered primarily in the deep offshore waters of the eastern Gulf of Alaska and partially in the adjacent Northeast Pacific Ocean over a period of 151.9 days ± 31.6 with spring migrations starting by late March. Males and females showed consistent spatial distributions within seasons, especially during winter. Tufted puffins shifted southwards throughout the non-breeding season, similar to other Atlantic and Northeast Pacific alcids. Our study provides important information on the at-sea non-breeding phenology and distribution of tufted puffins, which can inform risk assessments for the species including vulnerability to spatially and temporally explicit marine pollution, disease, fisheries by-catch, and ocean-climate variability.